Economic position of LLP «Motor transport» in Kazakhstan - Salimbekova, D.I.; Srailova , G.N. (BUKETOV BUSINESS REVIEW, 2019)
The article studies the theoretical concepts of economic and financial analysis. The types of economic analysis in Kazakhstan are considered. Economic indicators of economic object are calculated. On the basis of financial data of LLP «Carrier» the analysis of liquidity and solvency of the balance sheet. Then financial stability, business activity is considered. The final stages of the analysis were profitability and profitability calculations. The assessment of the financial situation for 2018 in LLP «Motor transport»is given. The recommendations contributing to the improvement of economic activity of LLP «Motor transport» in the market conditions for the further preservation of the competitiveness of the enterprise. In connection with this, by restoring solvency, it was proposed to conduct an inventory of assets and liabilities of a company in a timely manner, as well as to convert low-liquid assets into cash and to repay short-term liabilities with their help. To improve financial sustainability, it is necessary to reduce production costs and reduce current financial needs, optimize the number of employees, convert debt into authorized capital, and strive for timely advance payments from customers. To ensure financial equilibrium for a long period of time, it was recommended to implement measures in the field of marketing, to attract additional investments for technological improvement.